UV Curable Coatings: Swelling studies, Gel content and Hardness - D. Kumar, G. Saravanan, R. Arun Kumar, S. Rajendran (International Journal of Control and Automation, 2020)
Several formulations were prepared from the prepolymer, 2,2-bis-[4-(2-hydroxy-3-acryloxy prop-1-oxy)phenyl] propane with various functional diluents namely, di(ethylene glycol)ethylether acrylate, tri(ethylene glycol) dimethacrylate and trimethylolpropane ethoxylate (1-ethoxylate/hydroxyl) triacrylate in the presence of photoinitiator, 2, 2-dimethoxy-2-phenylacetophenone. These solutions were coated on the glass plates and then cured under ultraviolet radiation. The gel content (%), hardness and density of the photocrosslinked polymers were studied. The swelling coefficient, crosslink density and molecular weight between crosslinks of the photocured polymers were determined by swelling measurement using N, N’–dimethyl sulphoxide as a solvent. It is found that density, hardness and the gel content increases with increase of functionality in the diluent.